Percutaneous Drainage of Abdominal Collections under Imaging Guide - Meazher, Nasser M.; Mahdi, Mohammed A.; Al Obaidi, Safa M. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: One of the most significant advances in the treatment of intra-abdominal collections during the past 2 decades has been the introduction of image-guided therapy with percutaneous catheter drainage. The development of improved imaging modalities, together with broad-spectrum antibiotics and soft drainage catheters, has changed the treatment of collections that previously required an urgent operation. Disease processes that have traditionally been treated with open surgical drainage and debridement can now be resolved with percutaneous catheter drainage and antibiotics. In selected cases, this will allow for better preparation of the patient for a later elective and definitive operation. Objective: Highlight the outcome, safety and effectiveness of percutaneous drainage procedure of abdominal collections performed under imaging guide. Patients and Methods: Forty one patients were referred from surgical wards and emergency department after diagnosing abdominal collections. Then each case discussed with radiologist to determine the route and type of catheter and imaging modality for guidance (ultrasound and/or computerized tomography). The size and site of the collections were estimated along with the most suitable approach and angle of catheter insertion. A safe drainage route was identified avoiding solid organs and bowel. Results: Percutaneous drainage of 41 abdominal collections under imaging control was carried out in 41 patients during a one year period. No complications resulted from the procedure itself. Percutaneous drainage was sufficient to drain the collections in 35 cases (no further surgery is needed). Of those who require surgery (5 patients), the procedure considered to be as a temporary measure. One case was diagnosed as sero-mucinous tumor of bowel. Conclusion: Percutaneous drainage of abdominal collections is a safe, effective and minimally invasive alternative approach to formal surgical drainage.The advantages include: the drainage can be done under local anesthesia, diagnosis and treatment can be achieved simultaneously in radiological department.